2016
DOI: 10.1111/mec.13804
|View full text |Cite
|
Sign up to set email alerts
|

Tests of species‐specific models reveal the importance of drought in postglacial range shifts of a Mediterranean‐climate tree: insights from integrative distributional, demographic and coalescent modelling andABCmodel selection

Abstract: Past climate change has caused shifts in species distributions and undoubtedly impacted patterns of genetic variation, but the biological processes mediating responses to climate change, and their genetic signatures, are often poorly understood. We test six species-specific biologically informed hypotheses about such processes in canyon live oak (Quercus chrysolepis) from the California Floristic Province. These hypotheses encompass the potential roles of climatic niche, niche multidimensionality, physiologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
54
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 92 publications
(243 reference statements)
1
54
0
Order By: Relevance
“…For example, the Euclidean distance between georeferenced locations often does not capture the geographic isolation experience by organisms (McRae 2006). changes in population size and dispersal probabilities) differ across heterogeneous landscapes and/or during colonization (Neuenschwander et al 2008, He et al 2013, Bemmels et al 2016. Likewise, with very little overlap between past and present distributions (Fig.…”
Section: Validation and Interpretation Of Model-based Tests Of Biologmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the Euclidean distance between georeferenced locations often does not capture the geographic isolation experience by organisms (McRae 2006). changes in population size and dispersal probabilities) differ across heterogeneous landscapes and/or during colonization (Neuenschwander et al 2008, He et al 2013, Bemmels et al 2016. Likewise, with very little overlap between past and present distributions (Fig.…”
Section: Validation and Interpretation Of Model-based Tests Of Biologmentioning
confidence: 99%
“…Moreover, our tests of which models we are more probable does not mean we have necessarily identified 'the correct' model Maddison 2002, Beaumont et al 2010), even with validation procedures to evaluate that the models are capable of generating the data (Oaks et al 2013, Bemmels et al 2016; this is true for any model-based inference procedure and is not specific to the approach we apply here. Moreover, our tests of which models we are more probable does not mean we have necessarily identified 'the correct' model Maddison 2002, Beaumont et al 2010), even with validation procedures to evaluate that the models are capable of generating the data (Oaks et al 2013, Bemmels et al 2016; this is true for any model-based inference procedure and is not specific to the approach we apply here.…”
mentioning
confidence: 99%
“…Canyon live oak is a widely distributed tree in California, with relictual populations in Arizona, Nevada, New Mexico, Oregon and northern Baja California (Thornburgh, ; eFloras, ). Previous microsatellite‐based studies have shown that this species presents a deep genetic structure, with two genetic clusters separating populations located north and south of the Transverse ranges (Ortego et al ., ; Bemmels et al ., ). This phylogeographical subdivision contrasts with the shallow patterns of genetic differentiation found among other Californian oak species with similar distribution ranges, including both red oaks (section Lobatae ; Dodd & Kashani, ) and white oaks (section Quercus ; Ashley et al ., ; Fitz‐Gibbon et al ., ; Ortego et al ., ; but see Gugger et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…We hypothesize that interspecific gene flow may have occurred due to increased geographical contact between the two species during the Miocene/Pliocene epochs (23.03–2.58 Myr ago (Ma)), when Q. tomentella was widely distributed in continental California (Axelrod, ,b; Muller, ; eFloras, ), and/or during the Pleistocene glacial periods (2.59–0.01 Ma), when the lower sea levels almost connected the northern Channel Islands (Santa Rosa, Santa Cruz and Anacapa) to the mainland (Johnson, ). We (3) also explore whether the deep genetic structure of Q. chrysolepis reported in previous studies (Ortego et al ., ; Bemmels et al ., ) represents a phylogeographical break driven by the past geological history of the region and/or hides a cryptic history of hybridization or introgression with Q. tomentella (Calsbeek et al ., ; Chatzimanolis & Caterino, ; Vandergast et al ., ). Finally, we (4) test whether lineages/populations involved in hybrid gene flow interactions show higher levels of genetic diversity than those that have not experienced genetic admixture (Nettel et al ., ; Streicher et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the x ‐ origin pipeline differs in that (i) it infers a novel model parameter of interest Ω (i.e., the actual latitudinal and longitudinal coordinates), and (ii) it utilizes information from spatial summary statistics, specifically, pairwise population measures of F ST and the directionality index, Ψ (Peter & Slatkin, ). As such, x ‐ origin is an approach that focuses on the estimation of a specific parameter of interest—Ω, whereas the iDDC is an approach for model selection among a set of biologically informed demographic hypotheses, the foci of which vary significantly among studies (e.g., Bemmels, Title, Ortego, & Knowles, ; Knowles & Massatti, ; Massatti & Knowles, ).…”
Section: Introductionmentioning
confidence: 99%